FİZYOTERAPİ VE REHABİLİTASYON EĞİTİMİNDE E-ÖĞRENME STİLLERİ İLE AKADEMİK PERFORMANS VE ALGILANAN ÖĞRENME DÜZEYLERİ ARASINDAKİ İLİŞKİNİN İNCELENMESİ - YİNANÇ, Satuk Buğrahan; ÖZÜDOĞRU, Anıl (Turkish Journal of Physiotherapy Rehabilitation, 2023)
Purpose: In our research, we aimed to investigate the dominant learning styles of students in physiotherapy and rehabilitation education conducted with distance education, to compare learning styles with academic performance and perceived learning levels. Methods: The data of our study were collected online during the spring semester final exams week of the 2020-2021 academic year. 352 students in the physical therapy and rehabilitation department of Kırşehir Ahi Evran University were reached online. E-Learning Styles Scale for Electronic Media, Perceived Learning Level Scale, and demographic information form were used in our research. In order to evaluate academic performance, weighted semester grade point average information was obtained. Results: 300 students who completed the online questionnaire and met the study criteria were included in our study. 75% of the included students are female and 25% are male. It was found that the majority of the students used the logical learning style (35.7%). Academic performance 78.30 ± 19.20; the perceived learning level was found to be 42.08 ± 7.96. There was no relationship between active learning and intuitive learning styles with academic performance and perceived learning levels (p>0.05), but a positive relationship was found with other learning styles. It was observed that the perceived psychomotor learning levels of the students using social learning and independent learning styles were significantly higher than the students using the audio-visual learning style (p=0.02). Conclusion: Although physiotherapy students commonly prefer logical learning styles during the distance education period, it has been observed that students who prefer audio-visual and verbal learning styles have higher academic performance. Although it was observed that the academic performance levels of the students using the audiovisual learning style were higher, the perception of psychomotor learning was found to be low when compared with the students using the social and independent learning style. Psychomotor learning has an important place in physiotherapy education. Problems experienced in psychomotor learning may cause problems in the realization of practices in the physiotherapist profession.